Förbättrad på- och avstigning för rullstolsburna på Västtrafiks bussar - Eriksson, Linus; Hultgren, Linus (My University, 2023)
This thesis covers a product development project at the program Product Development and Design at Chalmers tekniska högskola and handles an examination project provided by Västtraffik. In the thesis the ramp intended for wheelchair use on public transport was studied, buses specifically, through observations and interviews with users and bus drivers. This was done to get an understanding for the problem and produce a concept building upon user needs. The goal of the project was to improve for wheelchair users in traveling with public transport and buses in Gothenburg by initiative of Västtrafik, who found the system inadequate. In doing the project the group got an understanding for the mental and physical strains associated with traveling with public transport as a wheelchair user, which not only was grounded in the design of the ramp, but the system. By offering and allowing the user to be able to travel independently with the help of an electric ramp built into the bus and guaranteeing the lowering of the bus’s side, is the feeling of anxiety for many alleviated, in turn decreasing the mental and physical strain put on the user and the bus driver. The thesis resulted in a concept for an electrical ramp able to be extended with the help of buttons on the in- and outside of the bus, or by manually extending it by pulling on it. Therefore ensuring that the ramp always can be used. The thesis offers understanding of the problem and reflects over possible solutions the group found. This was done to encourage further developments within the field and to contribute to a more socially sustainable society